2022
DOI: 10.22159/ijap.2022v14i1.41243
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Tigecycline and Its Potential Impurities by a Stability-Indicating Rp-HPLC-Uv Detection Technique

Abstract: Objective: Stability representing the RP-HPLC method was established for synchronized quantification of Tigecycline and its impurities. This method was confirmed for its applicability to both tablet dosage and bulk drug forms. Methods: Intended for an isocratic elution, a mobile phase containing methanol: 10 mmol Triethylamine Buffer mixture (75:25 v/v, pH 6.1) was used at 1 ml/min flow rate and Agilent ZORBAX Eclipse XDB C18 (250 mm × 4.6 mm, 5 μm) column. Results: At 231 nm as wavelength, high-pitched peaks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The limit of quantitation (LOQ) and limit of detection (LOD) values were assessed for zanubrutinib, and its specified impurities were tabulated (table 13). These values were calculated from the slope (σ) and standard deviation (SD) method [29][30][31][32]. The following formula is used for the calculation of LOD and LOQ [26].…”
Section: Limits Of Quantification and Detection (Loq And Lod)mentioning
confidence: 99%
“…The limit of quantitation (LOQ) and limit of detection (LOD) values were assessed for zanubrutinib, and its specified impurities were tabulated (table 13). These values were calculated from the slope (σ) and standard deviation (SD) method [29][30][31][32]. The following formula is used for the calculation of LOD and LOQ [26].…”
Section: Limits Of Quantification and Detection (Loq And Lod)mentioning
confidence: 99%
“…9 , 10 TGC was previously determined using spectrophotometric methods, 11 fluorescence determination, 12 14 and liquid chromatography coupled with ultraviolet (HPLC-UV) 15 and mass spectrometry detection in human plasma (LC-MS-MS) 16 26 and pharmaceutical preparations. 27 – 32 Other methods, such as stability-indicating, 33 40 have also been used to determine the drug's parenteral dosage form. These analytical methods take significant time, are harmful to the surrounding ecosystem, and require using acetonitrile as a mobile phase.…”
Section: Introductionmentioning
confidence: 99%
“…Greenness assessment and QbD are essential aspects during method development. There is some interest in publishing the manuscript which, however, it also has a number of significant shortcomings that should be addressed before the manuscript is acceptable for indexing: While authors summarize a comparison between their suggested method and the previously published ones, they missed this article 1 that was published in International Journal of Applied Pharmaceutics 2021. I ask the authors to add it illustrating the difference between their work and the aforementioned article.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 The USFDA established Pharmaceutical Current Good Manufacturing Practices (cGMPs) over 21 st century in 2002, which led to the discovery of QbD. 13 Analytical QbD (AQbD) contains six stages of comprehensive development of an analytical method with improved performance and strong resilience. 14 Utilizing the QbD methodology reduces the duration necessary for creating an effective analytical technique and is also deemed an economical manner of guaranteeing quality at the outset, belonging to the method development perspective.…”
Section: Introductionmentioning
confidence: 99%